EVALUASI KERJA PADA ALAT GRATE COOLER DI PABRIK BATURAJA II PT SEMEN BATURAJA (PERSERO) TBK - Tanthowy Z, Thoriq Verel; Anugrah, Rendotian; Safaruddin, Safaruddin (Jurnal Multidisipliner Bharasumba, 2022)
Semen Baturaja (Persero) Tbk. is one of the industries in Indonesia which is engaged in cement. The cement production process at PT. Semen Baturaja (Persero) Tbk. divided into several stages, namely mining of raw materials, breaking of raw materials, drying of raw materials, mixing of raw materials, burning and cooling, grinding of semi-finished materials, and bagging cement. PT. Semen Baturaja (Persero) Tbk. (Persero) produces cement with raw materials in the form of limestone and clay obtained from the Company's limestone and clay mining site which is located about 1.2 Km from the factory in Baturaja, South Sumatra. Grate cooler is a type of clinker cooler that serves to cool the clinker quickly (quenching) in the cement production process. The cooling process in the grate cooler is an important part in determining the quality of cement. Clinker cooler efficiency is the ratio between the amount of heat returned to the kiln along with secondary air as kiln fuel air and tertiary air as calciner fuel to the amount of heat stored in the clinker when it enters the cooler inlet. The Grate Cooler is one of the main tools in the manufacturing process. cement. In the cement manufacturing process, there is a standard that has been set to determine the type of cement produced. In order to produce cement according to predetermined standards, the things that need to be considered are various aspects in the manufacturing process, including the composition of the materials used in the process. In addition to this, the heating and cooling processes in the clinker manufacturing process must also be considered.